PENGARUH OPINI AUDIT DAN AUDIT REPORT LAG TERHADAP VOLUNTARY AUDITOR SWITCHING DENGAN FINANCIAL DISTRESS SEBAGAI PEMODERASI PADA PERUSAHAAN PERINDUSTRIAN YANG TERDAFTAR DI BEI - Mahariyani; Afrah Junita; Tuti Meutia (Jurnal Mahasiswa Akuntansi Samudra, 2022)
The purpose of this study was to examine the effect of Audit Opinion and Audit Report Lag on Voluntary Auditor Switching with Financial Distress as a moderating variable. The data analysis method used is the classical assumption test such as: data normality test, multicollinearity test, autocorrelation test and heteroscedasticity test as well as hypothesis testing such as multiple linear regression test, interaction test or what is commonly called moderated regression analysis, individual parameter significant test (partial test), simultaneous significance test (simultaneous test) and coefficient of determination test (R2). The result of the multiple linear regression equation is Y= -0.915 + 0.024 X1 + 0.016 X2 - 0.088 M - 0.023 X1*M + 0.001 X2*M + e. Partially, audit opinion has no significant effect on voluntary auditor switching, audit report lag has no significant effect on voluntary auditor switching and financial distress has no significant effect on voluntary auditor switching. Based on the moderated regression analysis test partially financial distress cannot moderate the effect of audit opinion on voluntary auditor switching and financial distress cannot moderate the effect of audit report lag on voluntary auditor switching and simultaneously financial distress cannot moderate the effect of audit opinion and audit report lag on voluntary switching auditors.